Makanan Lokal “Tatake” sebagai Daya Tarik Wisata Kuliner di Desa Botutonu’o Kabupaten Bone Bolango - Yumanraya Noho; Meilinda L. Modjo; Poppy Arnold Kadir (Ideas Publishing, 2021)
Gorontalo is a tourist destination that is rich in both, nature and culture. One of the cultural attractions that are quite popular in Gorontalo is culinary. Botutonu'o village which is located in the coastal area of ​​Tomini Bay, Kabila Bone District, Bone Bolango Regency has a unique local food appeal that has not been widely explored and introduced to the community. It is a type of dish made from shellfish or what the local community calls